Crime prevention on college campuses: correlates of problem-solving, environmental design, and anti-fear efforts by campus law enforcement - Reyns, Bradford W. (Crime prevention and community safety, 2021)
The current study examines factors related to crime prevention activity by law enforcement agencies serving institutions of higher education throughout the USA. Identifying facilitators and barriers to the implementation of crime prevention programs and practices will be useful to proponents of these approaches. Using data collected by the Bureau of Justice Statistics from a large sample of agencies throughout the USA, we identify factors that are related to applied forms of crime prevention, including crime prevention through environmental design, problem-oriented policing, use of SARA, having a crime prevention unit within the agency, and participation in anti-fear campaigns. Particular attention is placed on the effects of campus characteristics, agency characteristics, campus crime, precautionary actions, and other law enforcement precautionary activities. Results suggest that, overall, more task-oriented agencies are also more likely to engage in crime prevention activity, although the determinants of crime prevention varied by activity.